2018
DOI: 10.1186/s41199-018-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in patients with high risk HPV-associated and HPV negative oropharyngeal and oral cavity squamous cell carcinomas

Abstract: Background: Human papilloma virus (HPV)-associated head and neck cancer is now recognized as a distinct clinical entity from HPV-negative tumors, which are primarily associated with tobacco and alcohol exposure.Little is known, however, about the behavior of HPV-associated oropharynx (OP) and oral cavity (OC) SCCs as two distinct cancers and how sex affects the overall survival (OS) in these two cancers. The objective of our study is to determine if sex is associated with overall survival (OS) in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
(29 reference statements)
3
17
0
1
Order By: Relevance
“…Similar findings of low HPV integration rates have been reported in OC patients when compared to OPC patients [49,51]. This is further supported by previous reports of no statistically significant differences in prognostic and survival outcomes between HPV-negative and -positive patients with non-OPC conditions, including OC [52][53][54]. Indeed, a recent study demonstrated that HPV is uncommonly associated with the oncogenesis of OC [55].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings of low HPV integration rates have been reported in OC patients when compared to OPC patients [49,51]. This is further supported by previous reports of no statistically significant differences in prognostic and survival outcomes between HPV-negative and -positive patients with non-OPC conditions, including OC [52][53][54]. Indeed, a recent study demonstrated that HPV is uncommonly associated with the oncogenesis of OC [55].…”
Section: Discussionsupporting
confidence: 87%
“…To investigate the HPV type distribution in patients with OPMD and OC, a high-throughput MALDI-TOF mass spectrometry-based method (Mass Array Platform, Agena Bioscience, Hamburg, Germany) was used, as previously described [18]. This method is able to detect 16 HPV DNA types (HPV16, 18,31,33,35,39,45,51,52,53,56,58,59, 66, 68 and 73) in a single well.…”
Section: Low and High-risk Hpv Dna Genotypingmentioning
confidence: 99%
“…A more recent population study on data retrieved from the National Cancer Database (NCDB) from 2010 to 2014, representing over 70% of patients in the USA, shows a higher HPV positivity in men than in women for both OPSCC (66% vs. 50%) and OCSCC (16% vs. 11%). 67 In a cohort of 21,627 OPSCC patients, the prevalence of HPV-driven tumours is 6.3-fold higher in men than in women, whereas considering the 9080 OCSCC patients the ratio is reduced to a 2.6-fold change (Table 1). A higher prevalence in men has also been observed for HPV-negative OPSCC or OCSCC patients, albeit to a lesser extent (Table 1).…”
Section: Stratification Of Hpv-related Hnscc By Sexmentioning
confidence: 99%
“…A higher prevalence in men has also been observed for HPV-negative OPSCC or OCSCC patients, albeit to a lesser extent (Table 1). 67 Within all four categories of patients (HPV-positive OPSCC and OCSCC, and HPV-negative OPSCC and OCSCC), women are older at the age of diagnosis, but have cancers that are diagnosed at earlier tumour (T) and node (N) stages, compared with men. 67 In HPVnegative OPSCC cases, Kaplan-Meier analysis shows a significantly higher overall survival (OS) in men than in women (Table 1), diverging from a previous report, 68 although in that study patients were not stratified by HPV.…”
Section: Stratification Of Hpv-related Hnscc By Sexmentioning
confidence: 99%
“…The rate of HPV infection in oral cavity cancer was about 13.4% while the infection rate was 36.7% in oropharyngeal cancer in the United States. [20] The HPV infection rate in OSCC is lower than the oropharyngeal cancer. In female OSCC patients, the frequency of HPV infection (9.6%) was much lower than the male (15.8%).…”
Section: Discussionmentioning
confidence: 99%